Survival of thalassemia patients at Dr. Cipto Mangunkusumo Hospital: a single center retrospective study - Teny Tjitra Sari; Damayanti Angelina; Ludi Dhyani Rahmartani; Anna Mira Lubis; Pustika Amalia Wahidiyat (Paediatrica Indonesiana, 2026)
Background Thalassemia is a serious health challenge around the world, especially in countries within the “Thalassemia belt,” including Indonesia. The effectiveness of treatment for thalassemia is often measured by how well patients survive and thrive. However, the information is still limited on the survival of thalassemia patients in Indonesia. Objective To evaluate factors related to mortality risk,  characteristics and age distribution of thalassemia patients at Dr. Cipto Mangunkusumo National Central General Hospital (CMNH), Indonesia. Methods Using patient medical records from the Thalassemia Center of CMNH, covering the years 2017 to 2023, we examined patient characteristics, age distribution, and survival rates. To understand survival over time, the Kaplan–Meier and Cox regression tests were used. Results The 562 thalassemia patients studied had an average age of 18.3 years and 286 (51%) were male. The majority of patients (55.8%) had β-thalassemia. Most patients were between 11 and 20 years old (38.6%), and nearly half of them (49%) received deferiprone as their iron chelation therapy. Patients with mean serum ferritin ≥ 2,500 ng/mL (87.7%) had lower survival than patients with mean serum ferritin < 2,500 ng/mL (12.3%), but the difference was not statistically significant [hazard ratio (HR) 1.23; 95%CI 0.29 to 5.16; P=0.779]. Conclusion At CMNH, most thalassemia patients were adolescents or young adults, and β-thalassemia was the most common subtype. Patients with mean serum ferritin ≥2,500 ng/mL had a higher estimated mortality risk than those with lower levels (HR 1.23; 95% CI 0.29–5.16), although the association was not statistically significant.